2020
DOI: 10.3329/jsr.v12i3.43313
|View full text |Cite
|
Sign up to set email alerts
|

A Magnetized Dark Energy Type R/W Model with Polytropic Equation of State in Brans-Dicke Theory

Abstract: In this paper, we study the spatially homogeneous Robertson-Walker cosmological models with magnetized isotropic dark energy like fluid in the scalar-tensor theory of gravitation proposed by Brans-Dicke. Variable cosmological constant ᴧ and Polytropic equation of state have been used to find exact solutions of the models with volumetric expansion and power-law relation. The Physical and dynamical behaviors of the models have been discussed using some physical quantities like energy density, pressure, and coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…/ (36) From eqs. (19), (27), (28), and (33) the energy density, the EoS parameter and the skewness parameter are obtained as…”
Section: Physical and Geometrical Properties Of The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…/ (36) From eqs. (19), (27), (28), and (33) the energy density, the EoS parameter and the skewness parameter are obtained as…”
Section: Physical and Geometrical Properties Of The Modelmentioning
confidence: 99%
“…Investigation of the Kantowaski-Sachs cosmological model with bulk viscous and cosmic string in f(T) gravity framework is done by Bhoyar et al [26]. Recently, Dewri [27] studied the spatially homogeneous Robertson-Walker cosmological models with magnetized isotropic dark energy like fluid in the scalar-tensor theory of gravitation. Brahma and Dewri [28] also worked on a paper Bianchi Type -V Modified ( , ) model in Lyra manifold, that approach the ɅCDM ( Lambda cold dark matter) model.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic field [35][36][37] found in both galactic and intergalactic space has played a significant role in understanding the distribution of energy in the Universe. Numerous authors have explored the influence of magnetic fields on cosmological development in diverse circumstances, both theoretically and practically [38][39][40][41][42][43][44][45][46]; Melvin [47] has also revealed that matter was strongly ionized and seamlessly associated with the field during the development of the Universe.…”
Section: Introductionmentioning
confidence: 99%